2013
DOI: 10.1161/circulationaha.112.078857
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Energy Loss Index in Asymptomatic Aortic Stenosis

Abstract: Background— Aortic valve area index adjusted for pressure recovery (energy loss index [ELI]) has been suggested as a more accurate measure of aortic stenosis (AS) severity, but its prognostic value has not been determined in a prospective study. Methods and Results— The relation between baseline ELI and rate of aortic valve events and combined total mortality and hospitalization for heart failure resulting from the progression of AS was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 44 publications
3
90
1
3
Order By: Relevance
“…48 This index accounts for pressure recovery in the ascending aorta by including the ascending aortic size in the calculations. Recent work by Bahlmann and colleagues 49,50 from the Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) study, showed that energy-loss index improved the prediction of AV events by 13%, suggesting that this may be a promising parameter to be used clinically.…”
Section: Role Of Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…48 This index accounts for pressure recovery in the ascending aorta by including the ascending aortic size in the calculations. Recent work by Bahlmann and colleagues 49,50 from the Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) study, showed that energy-loss index improved the prediction of AV events by 13%, suggesting that this may be a promising parameter to be used clinically.…”
Section: Role Of Echocardiographymentioning
confidence: 99%
“…V článku, který nedávno publikovali Bahlmann a spol. 49,50 s údaji ze studie SEAS (Simvastatin and Ezetimibe in Aortic Stenosis), se uvádí, že index ztráty energie zpřesnil predikci příhod AV o 13 %, což naznačuje, že by se mohlo jednat o slibný parametr pro použití v klinické praxi.…”
Section: úLoha Echokardiografi Eunclassified
“…3 In the large multicenter prospective study published in this issue of Circulation, 4 Bahlmann and colleagues show that a decrease of 1 cm 2 /m 2 in ELI predicts a 6.06-fold increase in AVR, a 5.25-fold increase in aortic valve events, a 1.93-fold increase in total mortality, and a 2.28 increase in combined mortality and hospitalization for heart failure. The hazard ratios for AVR and aortic valve events were March 12, 2013 attenuated (≈2.0) but remained significant after adjustment for peak jet velocity or mean gradient, whereas those for mortality and hospitalization were unchanged.…”
Section: From the Fluid Mechanics Concept To Clinical Validationmentioning
confidence: 99%
“…3 **Cut point of ELI used for reclassification of stenosis severity in the previous study by Bahlmann et al 7 ***Best cut point of ELI to predict outcomes over a 4-year follow-up in the present study. 4 The black dashed line is the identity line.…”
Section: The Dilemma Of Inconsistent Grading Of As Severitymentioning
confidence: 99%
See 1 more Smart Citation